On Aesthetics in Chinese Calligraphy of Qin, Han, Wei and Jin Dynasties - Jun, Dong (International Journal of Culture and History, 2024)
Different historical periods in China had different artistic and cultural pursuits, as did calligraphy. Calligraphers of all ages practiced diligently, diligently pursuing a higher level of calligraphy art training, I can lament that this time in china is different from the past, in today's increasingly advanced science and technology, people have long forgotten to write this skill. Calligraphy has also sadly lost her dazzling glory of the times, there are now few calligraphy practitioners in the crowd. Therefore, with the passing of a group of modern calligraphy, there is no calligraphy in China for a hundred years to lead the times, it is really lamentable. In order to find the aesthetics in calligraphy, I had to start with ancient Chinese calligraphy. This paper will discuss the aesthetic features of Chinese calligraphy in Qin, Han, Wei and Jin dynasties.